Analisis Manajemen Risiko pada Pelaksanaan Proyek Peningkatan Jalan Rigid Pavement Ruas Wadungasri – Tambaksawah - Hamzah, M. Luthfi; Triana, Masca Indra (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
Road construction projects are an important part of infrastructure development and involve various risks during their implementation. Poor risk management may lead to project delays, cost overruns, decreased work quality, and disruption of project performance. Therefore, risk management analysis is required to identify and evaluate the risks that may occur during project execution. This study aims to analyze risk management in the implementation of the rigid pavement road improvement project on the Wadungasri – Tambaksawah section. The study employed a quantitative approach through questionnaire distribution to 30 respondents directly involved in the project implementation. Data analysis was conducted using the Severity Index (SI) method by combining probability and impact values to determine the risk level of each variable. The results indicate that 7 risk variables were classified into the high-risk category (43.75%), namely delays in equipment and material mobilization, low work productivity and efficiency, equipment damage in the field, delays in project progress, ineffective traffic management, ineffective work methods, and limited access to materials and equipment. Meanwhile, 9 other variables were categorized as medium risk, and no variables were classified as low risk. Based on the Severity Index ranking, several operational-related risk variables showed higher risk levels compared to other variables. Risk response strategies were mainly focused on mitigation efforts, including preventive equipment maintenance, improvement of material mobilization planning, periodic project progress monitoring, optimization of work methods, and traffic management around the construction area. Proper risk management is expected to improve project performance and support the achievement of project objectives effectively.